2021
DOI: 10.3389/fpsyg.2021.794353
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the HADS Measure of Anxiety and Depression Among Multiple Sclerosis Patients in Croatia

Abstract: Depression and anxiety are common complaints in patients with multiple sclerosis (MS). The study objective was to investigate the factor structure, internal consistency, and correlates of the Croatian version of the Hospital Anxiety and Depression Scale (HADS) in patients with MS. A total of 179 patients with MS and 999 controls were included in the online survey. All subjects completed the HADS and self-administered questionnaires capturing information of demographic, education level, disease-related variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
(116 reference statements)
1
8
0
Order By: Relevance
“…It also adds to the knowledge about PSQI in general by testing the models presented in previous reviews [ 24 , 26 ], including a new model of the bifactor structure, as well as exploring the measurement invariance between control subjects and pwMS. It would be recommended for future studies investigating sleep quality in pwMS to manage demographic, socioeconomic status, habits (i.e., smoking), physical activity, fatigue, anxiety, depression, quality of life, as well as cognitive aspects [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also adds to the knowledge about PSQI in general by testing the models presented in previous reviews [ 24 , 26 ], including a new model of the bifactor structure, as well as exploring the measurement invariance between control subjects and pwMS. It would be recommended for future studies investigating sleep quality in pwMS to manage demographic, socioeconomic status, habits (i.e., smoking), physical activity, fatigue, anxiety, depression, quality of life, as well as cognitive aspects [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has reported the Cronbach's alpha ranging from 0.82-0.83 for this scale. 36 Permission was sought for the use of the Indian-adapted Hindi version of the scale for this study. The Hindi version has been validated for Indian settings.…”
Section: Hospital Anxiety and Depression Scale (Hads)mentioning
confidence: 99%
“…The Fatigue Severity Scale (FSS) standard questionnaire was used to categorize patients into those with or without fatigue. The total FSS was the sum of the nine questions and the average FSS was calculated by dividing this sum by nine [30]. An average score equal to or more than four was considered as a positive indicator of fatigue, similar to previous research in the P4O2 COVID study [26].…”
Section: Variables In This Studymentioning
confidence: 91%